2014
DOI: 10.1517/14728222.2014.926889
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic role and therapeutic target of leptin signaling in colorectal cancer

Abstract: Stringent binding affinity of leptin/Ob-R and overexpression of leptin/Ob-R and their targets in cancer cells make it a unique drug target for prevention and treatment of CRC, particularly in obesity colorectal patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 146 publications
0
8
1
3
Order By: Relevance
“…Leptin inhibition resulted in a decrease in the growth of tumours in animal and human studies [30]. Although antibodies against leptin receptors have been developed, these have yet to be tested as a CRC treatment [31].…”
Section: Leptinmentioning
confidence: 99%
“…Leptin inhibition resulted in a decrease in the growth of tumours in animal and human studies [30]. Although antibodies against leptin receptors have been developed, these have yet to be tested as a CRC treatment [31].…”
Section: Leptinmentioning
confidence: 99%
“…These phenomena lead to the deregulation of leptin signaling, thereby significantly contributing to HCC progression through its crosstalk with multiple signaling pathways, as discussed in breast cancer 47 or colorectal cancer. 68 …”
Section: Interaction Between Leptin Signaling and Oncogenic Pathways mentioning
confidence: 99%
“…Importantly, epidemiological data has established a link between leptin over-expression and high risk of CRC 21 . Moreover, the promotion function of leptin on growth and migration of CRC has been elucidated 2225 . In consistent, we found that MPS-1 was correlated with circulating leptin level in CRC patients, especially in obese cases, but not in non-obese cases.…”
Section: Discussionmentioning
confidence: 99%